Supporting the development of program leaders in higher education: An action research case study. (October 2020) - Delaney, Deborah; Stewart, Heather; Cameron, Robyn; Cardell, Elizabeth; Carruthers, Samantha; Love, Anita; Pearson, Andrew; Calleja, Pauline
The higher education (HE) landscape continues to grow in complexity; thus, there is a need to improve the understanding of leadership in this context. This action research (AR) study was undertaken in a multi-disciplinary context of an Australian university to develop and evaluate an action learning (AL) project promoting leadership practice. An overview of AL is provided to situate the case study methodology and to demonstrate how it is used to develop leadership capabilities and benefit 'team learning'. The findings support the development of AR programs for leaders in the ever-changing environment of HE. The need for an understanding of what leadership is, the development of a learning community and the articulation of the learning processes are seen as essential to support leaders in their development. Leaders not only need to be reflective but also require a safe and trusting environment to support their quest for career progression, grants and awards.